Adaptation and Psychometric Properties of the Forms of Self Riticizing/Attacking and Self-Reassuring Scale - Saba Yasien, Salman Zia, Mamoona Yasmin, Maham (Pakistan Journal of Psychology, 2017)
The objective of this study was to translate and adapt Forms of Self Criticizing/Attacking and Self-Reassuring Scale (FSCRS) in Urdu language as well as to establish the psychometric properties of translated version of FSCRS. After following the standardized procedure of adaptation, psychometric properties were assessed by administering Urdu version of FSCRS on a sample of 245 adult students. The age of the participants ranged from 18 to 25 years with the mean age of 21.2 years. Demographic Information Form, Urdu version of Forms of Self Criticizing/Attacking and SelfReassuring, Siddique-Shah Depression Scale and Interaction Anxiousness Scale were used. To establish psychometric properties, Cronbach’s alpha and Pearson Product Moment Coefficient of Correlation were used. Internal consistency of three factors of FSRCS included Inadequate Self, Reassure Self, and Hated Self was .68, .70 and .51 respectively. Association of subscales of FSCRS with Siddique-Shah Depression scale and Interaction Anxiousness Scale was found significant. It is concluded that Urdu version of FSCRS is found to be reliable and valid measure to use with Pakistani adult population.